2021
DOI: 10.1007/s12015-021-10144-8
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Enhance Therapeutic Efficacy of Mesenchymal Stem Cells Transplantation in Rats With Intracerebral Hemorrhage

Abstract: Background Previous studies have showed the bene cial effects of mesenchymal stem cells (MSCs) on experimental intracerebral hemorrhage (ICH) animal. Enhancement of the treatment e cacy of MSCs in ICH is essential, considering the diseases association with high rates of disability and mortality. Some auxiliary methods to enhance the bene cial e cacy of MSCs have been introduced. However, the effect of electroacupuncture (EA) on the therapeutic e cacy of MSCs transplantation in hemorrhagic stroke and its potent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Previous studies have indicated that the transplantation of MSCs combined with EA stimulation promotes axonal regeneration and functional recovery of the injured spinal cord [ 24 , 25 ] and leads to a better therapeutic effect by increasing the expression of neurotrophic factors, regulating neurogenesis, and increasing the neural differentiation of transplanted cells in ischemic stroke compared with a single therapy [ 26 , 27 ]. We also confirmed that the combined treatment improves neurological function in rats with ICH in a previous study [ 28 ]. However, the exact mechanism by which MSCs combined with EA improve neurological function remains to be further explored.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have indicated that the transplantation of MSCs combined with EA stimulation promotes axonal regeneration and functional recovery of the injured spinal cord [ 24 , 25 ] and leads to a better therapeutic effect by increasing the expression of neurotrophic factors, regulating neurogenesis, and increasing the neural differentiation of transplanted cells in ischemic stroke compared with a single therapy [ 26 , 27 ]. We also confirmed that the combined treatment improves neurological function in rats with ICH in a previous study [ 28 ]. However, the exact mechanism by which MSCs combined with EA improve neurological function remains to be further explored.…”
Section: Introductionsupporting
confidence: 90%
“…Rat MSCs labeled with green fluorescent protein (GFP) (Cyagen Biosciences, China) [ 28 ] were removed from liquid nitrogen, thawed in a 37°C water bath, and then centrifuged. After centrifugation, MSCs were resuspended in alpha-minimum essential medium ( α -MEM) (HyClone) supplemented with 10% fetal bovine serum (FBS, HyClone), 100 mg/ml streptomycin, and 100 U/ml penicillin and incubated in a humidified atmosphere with 5% CO 2 at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, EA downregulated the expression of neurogenesis inhibitory molecules, including NogoA, lysophosphatidic acid, and RhoA, to improve the proliferation and differentiation of endogenous neural stem cells and synaptic plasticity in stroke rats ( Tan et al, 2018 ; Yang et al, 2022 ). Deng et al (2021) have reported that EA promoted differentiation of transplanted MSCs into neuron-like cells and expressions of BDNF and NGF proteins displaying therapeutic efficacy in ICH rats. Furthermore, Zhang et al (2015) suggested that the combination of direct stereotactic intracerebral injection of HUC-MSCs and minimally invasive hematoma aspiration was better than either therapy alone in reducing neuronal damage and improving neuronal functions.…”
Section: Mechanisms Of Mesenchymal Stem Cells In Intracerebral Hemorr...mentioning
confidence: 99%
“…With the common progress of acupuncture and evidence-based medicine, the clinical and basic researches on the treatment of ICH by EA continue to emerge, and the interpretation of its mechanism is also constantly improving. EA can exert neuroprotective effect on brain injury after ICH through many ways, such as anti-inflammation, antioxidation, antiapoptosis and increasing brain derived neurotrophic factor protein [17–19]. In this study, we found that EA could activate PPARγ/Nrf2/γ-GCS signaling pathway, inhibit microglia activation, reduce ROS production, and accelerate ROS clearance, thus alleviating oxidative stress response and the extent of myelin sheath damage, improve neurological function after ICH.…”
Section: Discussionmentioning
confidence: 82%